The Functions of Code-Switching in Rwandan EFL Classrooms: Insights from Teachers and Learners - Jean d'Amour Ndayisenga; Ouda Teda Ena (Hasanuddin University, 2024)
In multilingual settings, speakers frequently move between codes and languages during their frequent social interactions. Any circumstance in which speakers flip between accepted codes is now considered code-switching. Several studies have assessed and compared aspects of code-switching in EFL classrooms focusing on the perception of the teachers in a multilingual context. However limited studies examined the use of code-switching in EFL classrooms like Rwanda where three languages are officially used, and one native language is still the most dominant for all people. The current study uses qualitative methods to examine how teachers perceive different aspects of code-switching in multilingual classrooms to address the following questions: what types of code-switching do both teachers and students use in the classrooms and how do they perceive that phenomenon? The research participants in the interview were nine senior teachers from Groupe Scolaire Nyamirama and the data was collected by coding. The findings from the interview demonstrate that both intra-sentential and inter-sentential functions of code-switching are sometimes used to manage the language minority in the classroom, remaining united with the students, and the language learners' lack of proficiency. This study provides future researchers with suggestions and educational implications for EFL/ESL teachers.